Implementation of Child Marriage Policy in Palu City - Muhammad Reski Febriansyah; Fentiny Nugroho (International Journal Labs, 2025)
This study describes and analyzes the implementation of policies for preventing and handling child marriage in Palu City, specifically regulated in Mayor Regulation Number 34 of 2023. It also identifies supporting and inhibiting factors. The policy aims to improve the Quality of Families, especially in the Quality of Legal Structures dimension, given that Central Sulawesi Province’s Family Quality Index score is 71.80, categorized as only